2010
DOI: 10.1089/ars.2009.2956
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Hydrogen Sulfide in the Blood of Diabetes Patients and Streptozotocin-Treated Rats Causes Vascular Inflammation?

Abstract: Hydrogen sulfide (H(2)S) is emerging as a physiological neuromodulator as well as a smooth muscle relaxant. We submit the first evidence that blood H(2)S levels are significantly lower in fasting blood obtained from type 2 diabetes patients compared with age-matched healthy subjects, and in streptozotocin-treated diabetic rats compared with control Sprague-Dawley rats. We further observed that supplementation with H(2)S or an endogenous precursor of H(2)S (l-cysteine) in culture medium prevents IL-8 and MCP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
200
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(236 citation statements)
references
References 30 publications
18
200
0
1
Order By: Relevance
“…Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11). Our recent study reported that supplementation with H 2 S increases glucose utilization and decreases secretion of the proinflammatory biomarkers IL-8 and MCP-1 in adipocyte and monocyte cell models (11,19). These studies demonstrate that malfunctioning H 2 S homeostasis can contribute to the pathogenesis of vascular inflammation and impaired glucose metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11). Our recent study reported that supplementation with H 2 S increases glucose utilization and decreases secretion of the proinflammatory biomarkers IL-8 and MCP-1 in adipocyte and monocyte cell models (11,19). These studies demonstrate that malfunctioning H 2 S homeostasis can contribute to the pathogenesis of vascular inflammation and impaired glucose metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…The prediction would be that hydrogen sulfide generation is reduced in the kidney in diabetes. Previous studies have shown that plasma hydrogen sulfide level is lower in human subjects with type 2 diabetes (48,49) and in end stage kidney disease patients on hemodialysis (50). Relevant to diabetic kidney disease, hydrogen sulfide levels in the kidney are reduced in a chemical model of type 1 diabetes in the rat (8).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in H 2 S levels in diabetes have attracted attention. There is clear evidence that circulating levels of H 2 S are reduced in animal models of diabetes (24,(35)(36)(37). Notably, lower circulating H 2 S levels have been measured in plasma samples obtained from patients with type 2 diabetes mellitus (T2DM) (35,38).…”
Section: Discussionmentioning
confidence: 99%